2014
DOI: 10.1001/jama.2014.686
|View full text |Cite
|
Sign up to set email alerts
|

Ending Sales of Tobacco Products in Pharmacies

Abstract: Provenance and peer review Not commissioned; externally peer reviewed.Data sharing statement Additional data, including specific product placements in each store and de\identified survey responses, are available by emailing the corresponding author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 29 publications
(29 reference statements)
0
31
0
Order By: Relevance
“…To better align its health-promoting business activities with the products it sells[51], RI-based CVS Health implemented a supply-side tobacco control policy by banning tobacco sales in its stores. The present study sought to examine the potential impact of this policy on racial/ethnic and socioeconomic disparities in the density of tobacco outlets across neighborhoods in RI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To better align its health-promoting business activities with the products it sells[51], RI-based CVS Health implemented a supply-side tobacco control policy by banning tobacco sales in its stores. The present study sought to examine the potential impact of this policy on racial/ethnic and socioeconomic disparities in the density of tobacco outlets across neighborhoods in RI.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] In 2010, the American Pharmacy Association issued a policy statement urging all pharmacies to discontinue the sale of tobacco products. [3] The announcement by Rhode Island-based CVS Health (formerly CVS Caremark) that it will no longer sell cigarettes or tobacco-related products at its approximately 7,600 pharmacy stores nationwide[4] starting in September 2014 sparked considerable discussion. [5-9] Yet, the potential impact of the CVS Health policy action on smoking behavior as well as what this action means for other pharmacy retailers selling tobacco products remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Further, one national pharmacy chain in the USA removed tobacco from its shelves in 2014 6. Despite these advances, the vast majority of pharmacies in the USA continue to sell tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…Chain community pharmacies have discontinued the sale of tobacco, added primary care clinics, and redesigned the pharmacy to allow pharmacists to more easily interact with patients. 1–4 However, studies have shown that simply physically remodeling pharmacies does not result in improved pharmacist-patient interaction and patient counseling. 5–7 Authors cited interacting system factors such as inadequate personnel training and lack of both pharmacist and patient readiness to increase patient counseling as contributing factors for their study results.…”
Section: Introductionmentioning
confidence: 99%